HIGH-PERFORMANCE COMPONENTS OF HARDWARE MULTI-BIT SPECIFIC PROCESSORS FOR THE ADDITION AND MULTIPLICATION OF BINARY NUMBERS (Computer systems and information technologies, 2023)
The relevance of solving the priority improvement problem for functional and computational components of microelectronics for arithmetic and logic unit (ALU) of modern supercomputers is emphasized. It is shown that in the structures of ALU operations such as: comparison, multiplexing and adding affect the marginal productivity of ALU. It is substantiated that mathematical operations of addition, accumulation of sums, multiplication and division are crucial for ensuring extremely high speed of vector and scalar computers. The purpose of the work is the development of new calculation algorithms and microelectronic structures of multi-bit ALU coprocessors, which are characterized by extremely minimal parameters of speed, hardware and structural complexity. Such high-performance coprocessors are widely used as components of ALU when performing algorithmically complex calculations of statistical, correlation, spectral, cluster and entropy analysis. High-speed co-processors for multiplication and accumulation of digital data with the properties of crypto-protection of telecommunication channels are effectively used in the conditions of military operations and the modern information front, for example, in unmanned aerial vehicles, ground launchers and processors of air defense systems. The main areas for improving system characteristics of microelectronic components of the ALU processors of vector and scalar supercomputers are outlined. Structures of combinational and synchronized single-bit binary adders are systematized due to the characteristics of minimum hardware complexity and maximum speed. The theoretical foundations of double binary arithmetic are outlined. A new structure of a high-performance matrix multiplier based on synchronized adder-accumulators and Booth's algorithm is proposed, which is characterized by increased speed compared to known structures. Grounded perspective directions for further development improvement of the basic characteristics of the investigated class of computing equipment components.